2019
DOI: 10.1111/jocn.14964
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ experiences of the caring encounter in the ambulance service—A qualitative study

Abstract: Aims and objectives To explore the experiences of the caring encounter in the ambulance service among parents to children aged 0–14 years. Background The care provided by the ambulance team is often associated with emergency medicine, traumatology and disaster medicine. But to develop care in the ambulance service, it is imperative to understand what the parents want and value in the care for their child. Design A qualitative study design was used. Methods Interviews was used for data collection, 16 caring enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 30 publications
0
35
0
Order By: Relevance
“…We provided written standardised recommendations for commonly used medications in paediatric emergency medicine, ‘which has been shown to reduce administration errors’ [ 18 ]. EMS providers were encouraged to have a standardised approach to the clinical examination of children, and this may have increased the caregivers’ confidence in the ambulance team [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We provided written standardised recommendations for commonly used medications in paediatric emergency medicine, ‘which has been shown to reduce administration errors’ [ 18 ]. EMS providers were encouraged to have a standardised approach to the clinical examination of children, and this may have increased the caregivers’ confidence in the ambulance team [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Life-threatening events are infrequent among children [ 3 6 ]. Nonetheless, clinical examination of children with acute illnesses or injuries can be challenging for health care professionals who do not treat children on a daily basis and may be stressful in emergency settings [ 7 10 ]. The Children's Safety Initiative-EMS identified several educational priorities for EMS providers: paediatric airway management, responder anxiety when working with children and general paediatric skills, among others [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…There appeared to be disagreement with perceived support of relatives on scene, with some describing relatives as helpful (see quotations 48-53 of thematic synthesis in Supplementary Material). From the parent's perspective, they found that being involved helped the assessment of their child (Jepsen et al, 2019). Other clinicians however felt that relatives hindered the pain management process (see quotations 54-56 of thematic synthesis in Supplementary Material).…”
Section: Qualitative Synthesismentioning
confidence: 99%
“…Some clinicians stated that parents can be 'hysterical' (Holmström et al, 2019) and confrontational (Williams et al, 2012) which can inhibit the clinician's ability to effectively manage pain. Jepsen et al (2019) explored the parent's perspective of the care encounter with the ambulance service and highlighted the importance of a family-centred approach that included the child and parents. Therefore, clinicians should prioritise calming and relaxing the parents as this will likely be reflected in the child (Gunnvall et al, 2018).…”
Section: Qualitative Synthesismentioning
confidence: 99%
See 1 more Smart Citation